FACTORS AFFECTING BRAND LOYALTY IN THE INDONESIAN COFFEE SHOP INDUSTRY (A CASE OF MAXX COFFEE) - Rappoport, Alexander; Bernarto, Innocentius (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The purpose of this study is to examine the positive effect of experiential marketing on brand image, as well as to examine the positive effect of experiential marketing, and brand image on brand loyalty amongst Maxx Coffee consumers in Jakarta-Bogor-Depok-Tangerang-Bekasi or JABODETAEK area in Indonesia. The data was obtained through the distribution of questionnaire through Google forms. The number of samples collected was 210 respondents. Purposive sampling was applied to obtain the sample. Data analysis method by implementing the partial least square- structural equation modelling (PLS-SEM) approach. The results revealed that experiential marketing, and brand image have a positive effect on brand loyalty. Likewise, experiential marketing has a positive effect on brand image.